Pengaruh Kualitas Pelayanan, Citra Merek, dan Persepsi Nilai Terhadap Loyalitas Konsumen Pisang King Rengat - Kurnia Dewi; Airine Yulianda (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
Customer loyalty is a customer who not only repurchases an item and service but also has a positive commitment and attitude towards a service company, for example by recommending others to buy or use the service. Service quality is an effort to fulfill the needs and desires of consumers based on what is expected by consumers. Brand image is a representation of the overall perception of the brand which is formed from the information and experience of the brand. Value perception is a consumer assessment that is carried out by comparing the benefits / benefits that will be received with the sacrifices incurred for a product. So this perception of value has an impact on consumers deciding to buy or use a product or service. This research is a quantitative descriptive study with the sample in this study being the consumers of Banana King Rengat. This study aims to determine and analyze the effect of service quality, brand image and perceived value on consumer loyalty. Questionnaires and interviews were conducted to obtain primary data and some additional data were used as primary data. The research findings indicate that service quality, brand image and perceived value have a positive influence on consumer loyalty to Pisang King Rengat